Characteristics and prognosis of isolated aortic valve infective endocarditis in patients with bicuspid aortic valves: a propensity matched study - Bohbot, Yohann; Denev, Seyhan; Benvenga, Rossella M.; Philip, Mary; Michelena, Hector I.; Citro, Rodolfo; Habib, Gilbert; Tribouilloy, Christophe (Frontiers in Cardiovascular Medicine, 2023)
Introduction Bicuspid aortic valve (BAV) is the most common congenital heart disease with an increased risk of infective endocarditis (IE). Few data are available on isolated native BAV-IE. The aim of this study was to compare patients with tricuspid aortic valve (TAV) IE and BAV-IE in terms of characteristics, management and prognosis. Material and methods We included 728 consecutive patients with IE on isolated native aortic valve in 3 centres: Amiens and Marseille Hospitals in France and Salerno Hospital in Italy. We studied in hospital and long-term mortality before and after matching for age, sex and comorbidity index. Median follow-up was 67.2 [IQR: 19–120] months. Results Of the 728 patients, 123 (16.9%) had BAV. Compared with patients with TAV-IE, patients with BAV-IE were younger, had fewer co-morbidities and were more likely to be male. They presented more major neurological events and perivalvular complications (both p < 0.05). Early surgery (<30 days) was performed in 52% of BAV-IE cases vs. 42.8% for TAV-IE (p = 0.061). The 10-year survival rate was 74 ± 5% in BAV-IE patients compared with 66 ± 2% in TAV-IE patients (p = 0.047). After propensity score matching (for age, gender and comorbidities), there was no difference in mortality between the two groups, with an estimated 10-year survival of 73 ± 5% vs. 76 ± 4% respectively (p = 0.91). Conclusion BAV is a frequent finding in patients with isolated aortic valve IE and is associated with more perivalvular complications and neurological events. The differences in survival with TAV-IE are probably related to the age and comorbidity differences between these two populations.